Analog VLSI design automation. - Balkir, Sina, ....-; Dündar, Günhan, ....-; Selçuk Ögrenci, A., ....- (Boca Raton : CRC, 2003)
Samenvatting:The explosive growth and development of the integrated circuit marketover the last few years have been mostly limited to the digital VLSIdomain. The difficulty of automating the design process in the analogdomain, the fact that a general analog design methodology remainedundefined, and the poor performance of earlier tools have left the analogworld with few, if any, options for automated VLSI design.Analog VLSI Design Automation may well mark the dawn of a new era. Itdescribes a fully integrated, top-down approach to analog VLSI designautomation and presents a methodology for each level of the designhierarchy. The authors define an analog VLSI design automation flow inwhich every tool has its predefined objectives and interfaces. Theypresent working examples for each tool, and demonstrate the validity oftheir approach by running their design automation system from the top tothe bottom levels in three different case studies.Technologies like systems-on-a-chip (SOCs) have created a pressing needfor automated design tools capable of handling analog circuit blocks. Theideas presented in this book are fully adaptable to various designclasses. Using these ideas, you will be able to develop new methodologiesand algorithms that will significantly reduce design costs and time tomarket for many practical systems.
Keywords: Vlsi geïntegreerde schakelingen